PENGARUH ETOS KERJA TERHADAP KINERJA PEGAWAI KANTOR KELURAHAN BERINGIN RAYA - Rahma Fatria; Maria Elina; Husna Purnama; Hesti Widi Astuti; Tedi Gunawan (MANAJEMEN, 2024)
Because human resources are a very important and indispensable organizational asset to achieve goals, such as the vision and mission of the organization, the role and function of human resources cannot be replaced by other resources. Kelurahan has duties and functions to carry out government tasks delegated by the sub-district head, as well as other government tasks stipulated by law.Kecamatan and kelurahan have a hierarchical working relationship. This study aims to determine how work ethic affects the performance of Beringin Raya employees, totaling 25 people. The results show that work ethic affects employee performance positively and significantly. Work ethic is defined as an attitude that has meaning as an evaluation component owned by individuals or groups in providing an assessment of work.